Analisis Peran Guru dalam Pelaksanaan Pembelajaran pada Masa Pandemi Covid-19 di Kelas III SDN Gandasari 1 Kota Tangerang - Fartdilah, Kurnia; Nurfadhillah, Septy; Nuraeni, Yeni (ANWARUL, 2022)
This study aims to describe the role of teachers during the implementation of learning during the Covid-19 pandemic. This research uses qualitative research methods with a type of case study approach intended to accurately explain a particular individual phenomenon or characteristic, situation or group that occurs. The subject on this study was class III Teachers. Taknik data collection uses observation with 2 sources, namely teachers and students, interviews with 3 sources, namely principals, teachers, and students and using document studies. In this case, researchers conduct interviews to find out some indicators of the role of teachers, (1) Teachers as educators and teachers, here teachers play a role in providing a material to students with easy-to-understand language; (2) teachers as mediators or learning resources and facilitators, here teachers play a role in providing a way out in student learning activities that usually use package books in the delivery of materials; (3) teachers as models and role models, teachers play a role by setting a good example to their students; (4) teachers as motivators, teachers act as student encouragement in order to improve the development of student learning activities; (5) teachers as mentors and evaluators, teachers play a role to guide students to be able to determine the various potentials they have as student provisions.